STARS WITH VIGOROUS CONVECTION ENVELOPES AND RESULTS ON GENERAL MAGNETIC FIELD OBSERVATIONS - Plachinda, S. I. (Одеські астрономічні публікації, 2017)
Existence of the GMF on convective stars with vigorous convective envelopes confirms a conclusion that the GMF is a real phenomenon and reflects properties of a stationary global magnetic field, Origin Magnetic Field, of the Sun’, convective star’, radiative interior onto its surface. The presence of a variability of the longitudinal magnetic field measurements on ε Gem throughout the night is suspected.